Fingerprint recognition system - Rohani, Abu Bakar (2005)
Fingerprint recognition is the oldest method which has been used in numerous applications for identification purpose in many social conditions such as access control and crime investigation.Now a day,in the era of technology the system is still using the password or smart card as an identity character for identification purpose.The problems happen when user forgot their password or lost their smart card. To solve this problem,a prototype for recognition fingerprint was implemented the Fast Fourier Transform (FFT) technique for features extraction and Euclidean Distance for template matching.The waterfall methodology has been used in this prototype because it can provide an orderly sequence of development steps and help to ensure the and quality,reliability, maintainability.Features extraction algorithm will produce the reference number.In addition, template matching algorithm will do the comparison between the fingerprint image based on the reference number either it is similar or not.As a result of this technique, the input fingerprint image will be match with the store fingerprint image if there are the similar images.